PMC physics. (BioMed Central, a division of Biomed Central Ltd., 2007)
"PMC Physics B is an international, peer-reviewed, open access journal that publishes articles on condensed matter, atomic, molecular and optical physics and the interfaces between these areas."--Aims & scope (publisher's Web site, viewed Feb.27, 2008).